The Legal Situation Of The Consent Roya's Associates Against The Loss Of Liability Rights Certificate - Ida - Nursanti (Jurnal Akta, 2020)
This study aims to determine and analyze the legal position of Roya's Consent Deed on the loss of a Certificate of Mortgage; Notary authority in drawing Roya Consent Deed against the loss of a Certificate of Mortgage; as well as legal consequences arising from the loss of a Certificate of Mortgage? The research method used is sociological juridical research methods. Based on the research, it is concluded that the Roya Consent deed is a statement from the debtor in a notarized manner, which says that the debtor has been paid off of his debt and the creditor agrees to write off the certificate of land rights encumbered by the Mortgage to be a certificate which is clean from any kind of engagement. Roya's Consent Deed has no executorial power as does the Certificate of Mortgage; The notary's authority in making Roya's Consent Deed is based on the debtor's statement before the Notary so that the statement or act is contested by the Notary in an authentic deed. This is in accordance with the Law on Notary Position; the legal consequence of the Loss of Security Certificate for the debtor is unable to take legal action against his / her land rights, namely not being able to merit, or not being able to guarantee the right to his land or transferred to another party.